2016
DOI: 10.1186/s12864-016-2929-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of novel lncRNAs responding to phosphate starvation in Arabidopsis thaliana

Abstract: BackgroundPreviously, several long non-coding RNAs (lncRNAs) were characterized as regulators in phosphate (Pi) starvation responses. However, systematic studies of novel lncRNAs involved in the Pi starvation signaling pathways have not been reported.ResultsHere, we used a genome-wide sequencing and bioinformatics approach to identify both poly(A) + and poly(A)– lncRNAs that responded to Pi starvation in Arabidopsis thaliana. We sequenced shoot and root transcriptomes of the Arabidopsis seedlings grown under P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 88 publications
8
73
0
Order By: Relevance
“…In Arabidopsis thaliana, overexpression of lncRNA npc536 enhances tolerance to salt (Ben Amor et al, 2009). Moreover, genome-wide studies in A. thaliana have revealed hundreds of lncRNAs that respond to various external stimuli (Di et al, 2014;Yuan et al, 2016). Oryza sativa (rice) is an essential crop that grows in a wide range of environments characterized by various temperatures, salinity levels and soil/water conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana, overexpression of lncRNA npc536 enhances tolerance to salt (Ben Amor et al, 2009). Moreover, genome-wide studies in A. thaliana have revealed hundreds of lncRNAs that respond to various external stimuli (Di et al, 2014;Yuan et al, 2016). Oryza sativa (rice) is an essential crop that grows in a wide range of environments characterized by various temperatures, salinity levels and soil/water conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, by using strand specific RNA analysis on root tips, we succeeded in identifying thousands of different forms of lncRNAs: lincRNAs, NATs or antisense RNAs expressed from two Arabidopsis accessions, Col and L er . As previously shown in numerous studies, in comparison with mRNAs, lncRNAs observed here were expressed at low levels [62,63]. We opted to focus on root growth as it is a complex trait resulting of the expression of a large number of loci spread across the plant genome and is highly susceptible to the soil environment [64].…”
Section: Discussionmentioning
confidence: 96%
“…It acts as a target mimic for miR399, which regulates PHO2 mRNAs [81,82]. Moreover, Yuan et al [62] identified lncRNAs differentially expressed in root and shoot of plants grown in the presence or absence of Pi for 10 days. The authors suggested that a co-expression between lncRNAs and adjacent coding genes may be linked to a cis-regulation by lncRNAs of target genes involved in Pi starvation processes.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, various biological processes, including flowering time, immunity, fertility, root development and photomorphogenesis, have been shown to be regulated by lncRNAs (Swiezewski et al ; Heo and Sung ; Ding et al ; Zhou et al ; Bardou et al ; Wang et al ; Kim and Sung ; Seo et al )_ENREF_18_ENREF_23. Increasing evidence also implicates lncRNAs in the regulation of Pi homeostasis (Franco‐Zorrilla et al ; Jabnoune et al ; Shah et al ; Cruz de Carvalho et al ; Xu et al ; Yuan et al ; Wang et al ).…”
Section: Introductionmentioning
confidence: 99%